2018
DOI: 10.18202/jamal.2018.04.9020
|View full text |Cite
|
Sign up to set email alerts
|

Pencegahan Fraud Di Pemerintah Desa

Abstract: Pencegahan Fraud pada Pemerintahan Desa. Tujuan pene litian ini adalah untuk menelaah pengaruh sejumlah variabel terkait individu dan budaya terhadap kecenderungan fraud. Metode yang di gunakan adalah analisis regresi dummy berganda dengan 40 perangkat desa di Kecamatan Sayung, Demak sebagai sampel. Temuan utama dari penelitian ini adalah pemupukan moralitas individu perangkat pemerin tah desa yang baik dapat mencegah kecenderungan fraud. Upaya pemu pukan moralitas individu dapat dilakukan melalui pembinaan ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 21 publications
3
6
0
12
Order By: Relevance
“…This study is in line with previous findings which indicate the ethical culture of the organization has a significant negative effect on fraud (Julyana, 2015;Noviriantini et al, 2015) and morality has a negative and significant effect on fraud (Noviriantini et al, 2015;Wijayanti & Hanafi, 2018). While Akhsani (2018) found a positive and significant effect on the suitability of compensation for financial fraud.…”
Section: Jurnal Keuangan Dan Perbankansupporting
confidence: 91%
See 1 more Smart Citation
“…This study is in line with previous findings which indicate the ethical culture of the organization has a significant negative effect on fraud (Julyana, 2015;Noviriantini et al, 2015) and morality has a negative and significant effect on fraud (Noviriantini et al, 2015;Wijayanti & Hanafi, 2018). While Akhsani (2018) found a positive and significant effect on the suitability of compensation for financial fraud.…”
Section: Jurnal Keuangan Dan Perbankansupporting
confidence: 91%
“…Noviriantini et al (2015) found apparatus morality had a negative effect on fraudulent tendencies. Wijayanti & Hanafi (2018) also confirmed that individual morality had a significant effect on accounting fraud tendencies. The research hypotheses are: The theory of planned behavior explains that a person's behavior will be shaped by the norm's view.…”
Section: Jurnal Keuangan Dan Perbankansupporting
confidence: 61%
“…The more effective the environmental control in a village government, the less fraud that will occur. This is in line with the results of research by Wijayanti & Hanafi (2018) stating that the appropriate distribution of responsibilities and authority and conducting authorization from the authorities will result in a decreased level of tendency to fraud. The environment control also has a role in ensuring that an organization's activities are run in accordance with organizational goals (Rita et al, 2017).…”
Section: The Effect Of Environment Control On Fraud In Managing Villasupporting
confidence: 87%
“…Hal ini dapat diartikan bahwa jika variabel Keyakinan Hukum Karma Phala (X2) mengalami peningkatan dengan asum si bahwa variabel lainnya konstan, maka variabel terikat Keberhasilan Pengelolaan Dana Desa akan meningkat senilai 0,216. Konsistensi penelitian ini sejalan dengan argumentasi Atmadja & Saputra (2017) dan Wijayanti & Hanafi (2018) mengenai pence gahan fraud melalui peningkatan moralitas perangkat desa yang menjalankan peme rintahan. Peningkatan moralitas tersebut dengan cara melakukan pembinaan untuk para perangkat desa, seperti meningkatkan keimanan dan ketakwaan serta rasa syukur dan kesabaran.…”
Section: Hasil Dan Pembahasanunclassified